PENGARUH INTERNAL AUDIT DAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KOTA PADANG - Ummi Guskhairani; Dewi Zulvia (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research aims to test whether there is an influence of internal audit and accounting information systems on the quality of financial reports. The population in this study is the finance department who works for the Padang city government. The number of samples in this study was 150 respondents. The sampling technique uses a purposive sampling method. The research method used is quantitative with the data source in the form of primary data. The data analysis method uses multiple linear regression analysis with SPSS version 16. The results of this research provide empirical evidence that partially internal audit variables and accounting information systems have a positive effect on the quality of financial reports.